Membangun Semangat Anti Korupsi Melalui Ajaran Trilogi Karmaphala: (Analisis Fenomena Kasus Korupsi Yang Terjadi di Indonesia) - Anak Agung Gde Oka Widana (Jayapangus Press, 2022)
The phenomenon of corruption cases is not a foreign phenomenon in Indonesia. Its existence seems to have become ingrained in the daily routine of the world of work which is increasingly being suppressed by the increasing pace of development of the necessities of life, as well as the temptation of the development of new technological innovations that are increasingly tempting. There have been many cases of corruption that have been revealed, but the emergence of corruptors is actually getting more and more caught. Of course, it is interesting to study when considering the fact that criminal and civil law verdicts have not provided a deterrent effect. There is a need for the presence of other sanctions that accompany so that corruptors are more aware of, which in this case is the cultivation of an understanding of religious sanctions. The purpose of this research is to stimulate the anti-corruption spirit of the community through understanding the teachings of Hinduism, especially through the concept of the Karmaphala Trilogy. Three issues are raised in this study: the existence of corruption, efforts to eradicate corruption and efforts to build an anti-corruption spirit through the Karmaphala Trilogy. As a type of qualitative research, the data obtained in this study were collected through library techniques and document recording. The data that has been collected is then analyzed using a qualitative descriptive technique. The results of the analysis show that corruption is a product of the life attitude of a group of people who glorify the existence of nominal finance (money) as a standard of truth. Recognizing the increasingly worrying level of extremity of corruption cases, efforts to eradicate them can no longer be carried out with ordinary steps, but extraordinary methods are needed in the form of a combination of socialization of criminal law, civil law and religious law. Building the Anti-Corruption spirit through the Karmaphala Trilogy is one alternative that can be done, through inculcating an understanding of the concept of Sancita Karmaphala, instilling an understanding of the concept of Prarabdha Karmaphala and inculcating an understanding of the concept of kryamana karmaphala to the public.